ҚАРАҚАЛПАҚ ТИЛИ АРҚА ДИАЛЕКТИ СӨЙЛЕСИМЛЕРИНДЕГИ ФОНЕТИКАЛЫҚ ҚУБЫЛЫСЛАР - Қайпназарова, М.К. (SCIENCE and SOCIETY, 2016)
The article deals with the analysis of phonetic peculiarities of the northern dialects of the Karakalpak language and phonetic qualities of the vowels and consonants in comparison with the literary language.
Keywords: the north dialect of the Karakalpak language; phonetic peculiarities; phonetic qualities; literary language